2012
DOI: 10.1016/s0140-6736(12)61729-2
|View full text |Cite|
|
Sign up to set email alerts
|

Years lived with disability (YLDs) for 1160 sequelae of 289 diseases and injuries 1990–2010: a systematic analysis for the Global Burden of Disease Study 2010

Abstract: Bill & Melinda Gates Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
4,858
3
191

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 7,065 publications
(5,152 citation statements)
references
References 72 publications
30
4,858
3
191
Order By: Relevance
“…Depression is a common mental health condition and poses a considerable disease burden in terms of years lived with disability (Vos et al., 2012). Major depressive disorder (MDD) has a 12‐month prevalence of 5.1%, whereas the prevalence of subthreshold depression can be as high as 15% (Kessler & Bromet, 2013; Kessler et al., 2015; Shim, Baltrus, Ye, & Rust, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common mental health condition and poses a considerable disease burden in terms of years lived with disability (Vos et al., 2012). Major depressive disorder (MDD) has a 12‐month prevalence of 5.1%, whereas the prevalence of subthreshold depression can be as high as 15% (Kessler & Bromet, 2013; Kessler et al., 2015; Shim, Baltrus, Ye, & Rust, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The socio‐economic costs of migraine are enormous due to its high prevalence and disability during attacks 1, 2, 3. Acute pharmacological treatment is usually the first treatment option for migraine in adults.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study from this research group showed that visit‐to‐visit BPV significantly accelerated the progress of cerebral microbleeds rather than the progress of cerebral white matter lesions during follow‐up of 1.5 years 24. Considering the higher risk of hemorrhagic stroke in Chinese patients,1 it is necessary to analyze the association between SBPV and subtypes of stroke in China. Overall, 18.8% of stroke patients and 0.57% of all participants in our study had hemorrhagic stroke; these proportions are higher than existing data in this field (eg, 0.4% of all participants in the ASCOT‐PBLA study) 13.…”
Section: Discussionmentioning
confidence: 97%
“…Stroke is the leading cause of death in China and the second leading cause of death in the world 1. Almost 77% of strokes are first attacks; therefore, primary prevention is of great importance 2.…”
Section: Introductionmentioning
confidence: 99%